DETERMINAN PRAKTIK SEKS BERISIKO IMS (STUDI PADA ANAK JALANAN USIA 12-18 TAHUN DI RUMAH PERLINDUNGAN SOSIAL ANAK KOTA SEMARANG) - Aprilliana, Risma; Shaluhiyah, Zahroh; Indraswari, Ratih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Risky sexual behavior in street children is the behavior resulting from sexual desire both with the opposite sex and with the same sex. The Children's Social Protection House (RPSA) in Semarang City no longer focuses on street children in their teens, they focus more on children. The purpose of this study was to analyze the factors associated with risky sexual behavior for street children aged 12-18 years in the supervision and development of the Children's Social Protection House (RPSA) in Semarang City. The method in this research is quantitative research with a cross-sectional study approach and is carried out by taking a total population sampling technique. The population in this study was 50. The results showed that the practice of watching pornography videos (0,000), Knowledge of Reproductive Health (0,000), Knowledge of Sexual Behavior (0,000), Knowledge of Sexually Transmitted Infections (0,000), Peer Support (0.041), Family Support (0.032), Use of Information Media (0.001), Availability of Reproductive Health Services (0.006) have a significant relationship with STI-risk sex practices. This research concludes that the Office of Social Affairs must cooperate with health workers regarding the prevention of risky sexual behavior in street children and the need to provide reproductive health services in Child Social Protection Homes.